Fish Oil Ameliorates Doxorubicin Induced Memory Impairment in Wistar Rats: Life Sciences-Pharmacology - Marri, Jalaiah; Sharma, Jaya; Sharma, Pankaj (International Journal of Life Science and Pharma Research, 2022)
According to the World Health Organization, cancer is the leading cause of death in 112 countries under the age of 70 in 2019. Cognitive impairment is a common chemotherapeutic drug side effect that affects 15-80 % of cancer patients. These cognitive changes persist for one or two years following chemotherapy and sometimes persist for life time. Due to impaired cognitive function, survivors find utmost difficulty to perform day to day activities and lose their independency which has a negative impact on standard of living (SOL). The Antineoplastic drug doxorubicin has been associated with severe neurotoxicity, which manifests as a loss of cognitive abilities, most likely due to oxidative stress in the brain. Naturally occurring Omega-3 fatty acids have potential health benefits. They are abundant in fish oil. Fish oil is used as dietary supplement and is well known for anti-inflammatory, anti-hyperlipidaemia, cardio protective, and antioxidant and neuro protective functions. The current study explored to investigate Fish oil potential neuro protection and memory-improving advantages against Doxorubicin-induced cognitive and neurobiological impairments. The preventive effect of Fish oil against doxorubicin-induced memory impairments in rats was evaluated by using a novel object recognition task and the Morris water maze test. Doxorubicin-induced memory impairment was considerably prevented by fish oil treatment (50 mg/kg and 100 mg/kg). The levels of tumour necrosis factor (TNF-α) and acetyl cholinesterase activity were dramatically reduced with both dosages of Fish oil. Furthermore, Fish oil protected the frontal cortex and hippocampus parts of the brain from doxorubicin-induced oxidative and inflammatory damages. These findings suggest that Fish oil may be a promising adjuvant therapeutic option for decreasing doxorubicin-related side effects